PRINCIPLES OF REGIONALISM FORMATION IN EUROPEAN COUNTRIES AND CONSIDERING THEM FOR THE PRACTICE OF A NEW REGIONALISM FORMATION IN UKRAINE (International Journal of Innovative Technologies in Economy, 2018)
The article determines that new the institutional practices are being formed within individual states, a new regionalism with some common tendencies under the influence of globalization processes in European countries. It has been found out, that the European space is developing under the paradigm of new regionalism, which manifests itself both in the form of international cooperation and in the development of internal regionalization processes, in which the regions act as subnational territories. It is founded, that the new regionalism has accompanied in the European public opinion forming ideas for reform of the European Community on the liberalization of administrative organization United Europe, updating new regionalism, and the purpose statement regions as subjects of political, social, economic and administrative relations. This takes place in parallel with the process of regionalization through the establishment of independence from the central regions of national governments.